Bannon brothers : Trust - Dailey, Janet (New York : Kensington Books, 2011)
With the two-million-dollar reward for the safe return of Ann Montgomery, who was kidnapped long ago, about to expire, R.J. Bannon, agreeing to take on this cold case, believes that talented local artist Erin Randall is Ann--a discovery that brings a legacy of lies and deception to a shocking climax
Keywords: Missing persons -- Fiction; Cold cases (Criminal investigation) -- Fiction; Women artists -- Fiction; Private investigators -- Fiction; Kidnapping -- Fiction; Brothers -- Fiction; Missing persons -- Fiction